Conservation impact scores identify shortfalls in demonstrating the benefits of threatened wildlife displays in zoos and aquaria. Issue 7 (2nd July 2020) - Buckley, Kathryn A.; Smith, Liam D. G.; Crook, David A.; Pillans, Richard D.; Kyne, Peter M.
Abstract: Zoos and public aquaria globally display numerous wild harvested, threatened species. To validate conservation credentials, displays are often associated with research projects, educational interpretation, or conservation-related activities. However, accompanying conservation benefits are rarely assessed. In this study, an approach to evaluate conservation benefits of captive wildlife experiences is modelled by assessing four Australian aquarium displays of the Critically Endangered largetooth sawfish Pristis pristis . Conservation impact scores were calculated for research, education, and conservation-related activities. In a novel approach, sawfish-related education (gaining knowledge, changing attitudes, and intentions to change behaviours) was evaluated using a before and after study design (n = 2 229), and conservation impact scores were calculated using effect sizes. Although visitors to all aquariums demonstrated significant positive attitudinal changes, and at one site gained knowledge, no significant change in behavioural intentions were detected. Educational messages addressing attitudes and behaviours were mostly generalised and untargeted. Formative and ongoing evaluations are needed to develop and maintain targeted and relevant messages. With one exception, research projects and conservation activities were unlikely to contribute substantially to sawfish conservation due to limited support from the aquaria. We recommend that increased support is directed to projects that are targeted towards impactful conservation goals.